PERANCANGAN ANTARMUKA BERBASIS WEB PADA SISTEM INFORMASI PENILAIAN SASARAN KINERJA PEGAWAI UNTUK JABATAN FUNGSIONAL DOSEN POLITEKNIK JAMBI - Setia Budi, Bagus; Tanto, Tanto; Meilano, Rezagi (LPPM Politeknik Jambi, 2024)
Politeknik Jambi is the only Vocational College in Jambi Province. Lecturers at Politeknik Jambi require effective and efficient employee performance data processing, but still rely on Microsoft Excel. One of Excel's weaknesses is its inability to display data according to access rights, especially when used by three different parties: lecturers, assessors, and administrative staff. This research aims to design a user interface for an employee performance target information system for functional lecturer positions based on web platforms at Politeknik Jambi, using data collection methods such as observation, interviews, and documentation with a Software Development Life Cycle approach. It is hoped that this design will facilitate the work of lecturers at Politeknik Jambi and improve the effectiveness of the performance assessment system as well as information accessibility